Role of common and rare variants in SCN10A : results from the Brugada syndrome QRS locus gene discovery collaborative study - Behr, Elijah R.; Savio-Galimberti, Eleonora; Barc, Julien; Holst, Anders G.; Petropoulou, Evmorfia; Prins, Bram P.; Jabbari, Javad; Torchio, Margherita; Berthet, Myriam; Mizusawa, Yuka; Yang, Tao; Nannenberg, Eline A.; et al. (Cardiovascular research, 2015)
Brugada syndrome (BrS) remains genetically heterogeneous and is associated with slowed cardiac conduction. We aimed to identify genetic variation in BrS cases at loci associated with QRS duration. A multi-centre study sequenced seven candidate genes (SCN10A, HAND1, PLN, CASQ2, TKT, TBX3, and TBX5) in 156 Caucasian SCN5A mutation-negative BrS patients (80% male; mean age 48) with symptoms (64%) and/or a family history of sudden death (47%) or BrS (18%). Forty-nine variants were identified: 18 were rare (MAF <1%) and non-synonymous; and 11/18 (61.1%), mostly in SCN10A, were predicted as pathogenic using multiple bioinformatics tools. Allele frequencies were compared with the Exome Sequencing and UK10K Projects. SKAT methods tested rare variation in SCN10A finding no statistically significant difference between cases and controls. Co-segregation analysis was possible for four of seven probands carrying a novel pathogenic variant. Only one pedigree (I671V/G1299A in SCN10A) showed co-segregation. The SCN10A SNP V1073 was, however, associated strongly with BrS [66.9 vs. 40.1% (UK10K) OR (95% CI) = 3.02 (2.35-3.87), P = 8.07 × 10-19]. Voltage-clamp experiments for NaV1.8 were performed for SCN10A common variants V1073, A1073, and rare variants of interest: A200V and I671V. V1073, A200V and I671V, demonstrated significant reductions in peak INa compared with ancestral allele A1073 (rs6795970). Rare variants in the screened QRS-associated genes (including SCN10A) are not responsible for a significant proportion of SCN5A mutation negative BrS. The common SNP SCN10A V1073 was strongly associated with BrS and demonstrated loss of NaV1.8 function, as did rare variants in isolated patients.